International Education at Community Colleges Themes, Practices, and Case Studies - Raby, Rosalind Latiner; Valeau, Edward J. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book brings together distinguished scholars, community college practitioners, and emerging leaders to expand upon existing theories, provide reflection on practice, and demonstrate the dynamic nature of community college internationalization. There is a special challenge for United States community colleges to move from selected international programs that impact a few students to sustainable change that influences the entire college community. A key importance is realization that reform is not based on chance, but on intentional designs that are intended to guide future endeavors. The research, case studies, and experiences of the authors in this book are both inspiring and critical in the quest to encourage an academic shift for long-term change that promotes international literacy as an integral component of the community college and celebrates the needs of the changing local communities. .